2002
DOI: 10.1093/bja/88.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Addition of meperidine to bupivacaine for spinal anaesthesia for Caesarean section†

Abstract: Addition of meperidine 10 mg to intrathecal bupivacaine for Caesarean section is associated with prolonged postoperative analgesia but with greater intraoperative nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 22 publications
2
51
0
1
Order By: Relevance
“…Patients who had 5 µg of sufentanil had significantly longer duration of analgesia than those who had 10µg fentanyl. Yu et al in their study [14] showed that there was a significant difference in the effective duration of analgesia (defined as the time of intrathecal injection to the first patient controlled analgesia demand), following addition of 10mg pethidine to 2.0 ml of 0.5% hyperbaric bupivacaine (mean 234 minutes) compared with the addition of saline (mean 125 minutes) which was also the same in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Patients who had 5 µg of sufentanil had significantly longer duration of analgesia than those who had 10µg fentanyl. Yu et al in their study [14] showed that there was a significant difference in the effective duration of analgesia (defined as the time of intrathecal injection to the first patient controlled analgesia demand), following addition of 10mg pethidine to 2.0 ml of 0.5% hyperbaric bupivacaine (mean 234 minutes) compared with the addition of saline (mean 125 minutes) which was also the same in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Neuraxial administration of other opioids such as sufentanil and meperidine with local anaesthetics (LAs) has also been demonstrated to prolong early postoperative analgesia compared with the use of local anaesthetic agents alone [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In another similar study, Yu et al [11] found that the group receiving added meperidine had a greater incidence of intraoperative nausea or vomiting than did the group receiving added saline. Farzi et al [12] found no statistically significant difference in the occurrence of nausea and vomiting, and concluded that their occurrence during the operation may be partly due to surgical manipulation and peritoneal stimulation.…”
Section: Discussionmentioning
confidence: 91%
“…Previous results also suggested that intrathecal meperidine, in doses as low as 10 mg, could increase nausea or vomiting. (9,18). Increased nausea and vomiting may delay home discharge for outpatient surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of our study were to evaluate whether meperidine would prolong the duration of sensorial block as in conventional spinal anaesthesia (9) to prolong surgery duration and improve the feasibility of strict unilateral block.…”
Section: Introductionmentioning
confidence: 99%